Pengaruh Tactical Games Terhadap Keterampilan Bola Voli Di SMPN 5 Klari - Aji, Fabian Ismu; Fahrudin, Fahrudin; Mahardhika, Dhika Bayu (Universitas Hamzanwadi, 2025)
This study aims to determine whether the tactical games model has an effect on students' skills in learning volleyball at SMPN 5 Klari. This type of research uses quantitative research with a one group pretest posttest design. The sampling technique in this study uses the cluster random sampling technique, this study was conducted in 8 meetings with the first meeting (pretest) respondents filled out the GPAI questionnaire related to student skills in learning volleyball, after that they carried out volleyball learning for 6 meetings with treatment using the tactical games model for the learning, and after that the last meeting (posttest) respondents filled out the same GPAI questionnaire related to student skills in learning volleyball. The results of the pretest and posttest data analysis were carried out using the Paired Sample T-test hypothesis test. The average value of students' skills in learning volleyball before and after using the tactical games model had a significant increase of 3.21. The conclusion of this study is that the results of the posttest scores from each test instrument have the results of the Paired Sample T-test test with the output